Linguistic Structures in the Light of the Digital Transformation: Addressing the Conflict Between Reference and Change - Frank, Ulrich (The Art of Structuring: Bridging the Gap Between Information Systems Research and Practice, 2019)
Information systems are at the core of the digital transformation. To cope with the dynamics of new, emerging markets and ever changing requirements, it is often argued that agile approaches to software development are mandatory. Some even demand to develop information systems without conceptual models, because they were likely to be outdated even before the software is implemented. While such a proposal is not acceptable for serious reasons, conceptual modelling is indeed facing a remarkable challenge in times of change. On the one hand, economics demand for reuse and interoperability, hence, for stable references. On the other hand, freezing structures is likely to compromise a software system's adaptability. Based on an analysis of this conflict and further challenges, it will be shown how languages for conceptual modelling can be designed to support both, the need for reference and the demand for change.